Strategy in a Fishbowl An Invitation to Determine the Shape of IMIA in 2015 (Methods of Information in Medicine, 2006)
Objectives: The International Medical Informatics Association (IMIA) today is an inclusive organization that represents the medical and health informatics world through its multiple member countries as well as affiliate, corporate and academic institutions, plus working groups and regions. The IMIA leadership deemed this is an excellent time to create a strategic alignment of IMIA’s goals and in turn to create a framework of the IMIA agenda for the future.Methods: The process began in early 2004, with a survey distributed to all IMIA members seeking members‘ views. The initial views were presented to the IMIA Board and General Assembly at Medinfo 2004 in San Francisco, USA. A Strategic Planning Task Force was established to take forward the development of a Strategic Plan. Through a combination of e-mail exchanges, face-to-face planning-discussion sessions in Geneva, Switzerland, and Washington DC, USA, and use of mediated conference calls, the IMIA Strategic Plan was evolved.Results: The framework model (also known as the IMIA rainbow umbrella) seeks to represent, in visual and descriptive terms, the numerous possibilities for connections and integration. Knowledge is the central core of IMIA. All of our strategies, interactions and efforts, emanate from this knowledge core. Using a concentric circle model, the next circle (from the central core) represents science. This is followed by the application layer circle, then the impact layer/circle and finally the outermost circle represents the people layer. Another dimensionality of the IMIA Strategic Plan is the need to represent various key sectors. There are six sectors superimposed on the five concentric circle layers of IMIA’s integration and connection to others. These sectors represent: health (our vision), research and science, behavioral responsibility, education, relationships and reach.Conclusion: We are still at a relatively early stage of planning. The Strategic Framework and Plan will be discussed by the IMIA Board and the IMIA General Assembly meeting (November 2006).
Keywords: International Medical Informatics Association; strategic planning